Encouraging Multiculturalism and Diversity within Organizational Behavior Management. Issue 3 (1st October 2020) - Akpapuna, Merrilyn; Choi, Eunju; Johnson, Douglas A.; Lopez, Juan A.
ABSTRACT: Injustice related to racism and inequality has long plagued business, higher education, and society. Simply stating that one supports the cause of social justice is no longer sufficient – measurable change is now being demanded. In theory, organizational behavior management should be well-situated to help usher in behavior change at the individual and organizational level to achieve powerful outcomes related to social justice. Unfortunately, organizational behavior management has not done enough to address these challenges in either practice or research. There is a pressing need for change if the field is to support and represent the diversity of our populace and this requires the field to examine and address multiple barriers to inclusion. This paper seeks to elucidate some of the issues related to training, financial support, recruitment, retention, measurement of progress, support of emerging diverse voices, and self-reflection. It is proposed that many of the tools and techniques of organizational behavior management could be leveraged to help enact change for both those we serve and within our own community.